Tadabbur Al-quran Through Information Technology: A Pilot Study Among Selangor Islamic University Students - Rohana Zakaria; Mohd Asri Ishak; Sharifah Nurhidayah Syed Aziz; Mardhiah Yahaya; Hayati Hussin; Sofea Thanaa’ Saibon (akademiabaru.com, 2024)
Indexed by MyCite